2004
DOI: 10.1001/jama.292.19.2357
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental and Growth Impairment Among Extremely Low-Birth-Weight Infants With Neonatal Infection

Abstract: HE INCREASED SURVIVAL OF EX-tremely low-birth-weight (ELBW) infants (ie, weighing 401-1000 g at birth) has heightened awareness of the importance of assessing and improving long-term outcomes associated with prematurity. [1][2][3][4] It is estimated that as many as 15% of the most immature infants develop cerebral palsy (CP) and approximately half develop cognitive and behavioral deficits. [1][2][3][4][5] Cerebral white matter damage, identified by cranial ultrasound or magnetic resonance imaging, is a powerfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
970
13
31

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,358 publications
(1,051 citation statements)
references
References 57 publications
37
970
13
31
Order By: Relevance
“…3,[7][8][9][10] Preterm infants, known to exhibit a markedly increased risk for the development of severe infections, may critically depend on their innate immune response, as the presence of early-onset and nosocomial infections mainly determines acute and long-term morbidity and mortality in this population, especially regarding the development of neurological and pulmonary impairment. [17][18][19] Especially, the development of chronic lung disease in preterm infants is known to be triggered by infectious complications and ongoing inflammatory processes. 18,[20][21][22] The aim of the present study therefore was to investigate whether genetic variation within the MBL gene is associated with alterations of acute and long-term pulmonary morbidity in preterm infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,[7][8][9][10] Preterm infants, known to exhibit a markedly increased risk for the development of severe infections, may critically depend on their innate immune response, as the presence of early-onset and nosocomial infections mainly determines acute and long-term morbidity and mortality in this population, especially regarding the development of neurological and pulmonary impairment. [17][18][19] Especially, the development of chronic lung disease in preterm infants is known to be triggered by infectious complications and ongoing inflammatory processes. 18,[20][21][22] The aim of the present study therefore was to investigate whether genetic variation within the MBL gene is associated with alterations of acute and long-term pulmonary morbidity in preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to respond effectively to infectious hazards clearly determines acute and long-term outcome especially in preterm infants. [17][18][19] Thus, several studies revealed pre-and postnatal infections to contribute to the development of chronic lung disease in preterm infants, 18,[20][21][22] which mainly determines morbidity and mortality during the first year of life in this patient cohort. Bronchopulmonary dysplasia (BPD) is histologically characterized by decreased alveolar septation resulting in large saccular airspaces, representing a rupture of pulmonary development from the saccular to the alveolar stage.…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal variables possibly related to the outcome were: bronchopulmonary dysplasia (BPD), small for gestational age (SGA), abnormal cranial ultrasound (periintraventricular or parenchymatous hemorrhage or leukomalacia), male gender, use of mechanical ventilation, patent ductus arteriosus (PDA), septicemia with positive blood culture, and gestational age categorized as less than versus greater than or equal to 28 weeks, birth weight less than 750g, necrotizing enterocolitis, head circumference at birth below the 10 th percentile 15,16 .…”
Section: Methodsmentioning
confidence: 99%
“…Stoll et al 15 reported a 20% loss-to-follow-up rate in very low birth weight premature children at 18 to 22 months corrected age. The children we studied belong to a low-income population, and many of the families live on the outskirts of the city of Rio de Janeiro and have difficulty paying for transportation to the hospital.…”
Section: Study Limitationsmentioning
confidence: 99%
“…11 Late-onset neonatal sepsis is a significant risk factor for increased mortality and prolonged hospital stays, 12 although mortality is variable and related to the implicated pathogen. 13 In those who survive, there is poorer long-term growth and developmental outcomes, 14,15 with associated increased morbidity and increasing healthcare costs. 16 Prevention of CLABSI is a key objective for improvement of patient safety and reduction of mortality, hospital stay, and costs.…”
mentioning
confidence: 99%